Holocaust Drama : the Theater of Atrocity. - Plunka, Gene A. (Cambridge studies in modern theatre., 2009)
Placing Holocaust drama in its historical and cultural contexts, this book provides thorough analyses of over thirty seminal Holocaust plays.